2019
DOI: 10.1080/15548627.2019.1659614
|View full text |Cite
|
Sign up to set email alerts
|

ZNNT1 long noncoding RNA induces autophagy to inhibit tumorigenesis of uveal melanoma by regulating key autophagy gene expression

Abstract: Long noncoding RNAs (lncRNAs) are proved to be critical regulators in numerous cellular processes. However, the potential involvement of lncRNAs in macroautophagy/autophagy is largely unknown. Autophagy is a highly regulated cellular degradation system, and its dysregulation is involved in many human diseases, including cancers. Here, we show that the lncRNA ZNNT1 is induced by PP242 and MTORC1 selective inhibitor rapamycin in uveal melanoma (UM) cells. Overexpression of ZNNT1 promotes autophagy by upregulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 39 publications
(47 reference statements)
2
57
1
Order By: Relevance
“…Notably, also patient-derived serum samples from melanoma patients with high level of autophagy flux have shown high levels of these proteins [81], suggesting that they can serve as surrogates for intra-tumoral autophagy dynamics. Elevated autophagy accompanying melanoma progression has been associated with loss of galectin-3 [82], increased levels of sirtuin 1 (SIRT1) [83], SIRT6 [84,85], BNIP3 [86], and long non-coding RNA ZNNT1 [87], and enhanced activity of signaling pathways such as AKT, independent of the mutational status of BRAF [88]. A heterozygous loss of ATG5 enhanced melanoma metastasis and predicted poor overall patient survival [89].…”
Section: Autophagy In Melanomamentioning
confidence: 99%
“…Notably, also patient-derived serum samples from melanoma patients with high level of autophagy flux have shown high levels of these proteins [81], suggesting that they can serve as surrogates for intra-tumoral autophagy dynamics. Elevated autophagy accompanying melanoma progression has been associated with loss of galectin-3 [82], increased levels of sirtuin 1 (SIRT1) [83], SIRT6 [84,85], BNIP3 [86], and long non-coding RNA ZNNT1 [87], and enhanced activity of signaling pathways such as AKT, independent of the mutational status of BRAF [88]. A heterozygous loss of ATG5 enhanced melanoma metastasis and predicted poor overall patient survival [89].…”
Section: Autophagy In Melanomamentioning
confidence: 99%
“…Of targets, It is postulated that lncRNA PVT1 acts by repressing mi-RNA 17-3, which interacts with MDM2 and p53 proteins [71]. By promoting autophagy, lncRNA ZNNT1 has also been associated with in vitro UM cell death [73]. Other lncRNAs such as lncRNA FTH1P3 [74], lncRNA MALAT1 [75], or HOXA11-AS [76] have also been incriminated in UM tumorigenesis.…”
Section: Main Clinical Findingsmentioning
confidence: 99%
“…The role of autophagy in cancer varies from person to person. On the one hand, autophagy contributes to maintaining cellular homeostasis and can suppress tumor growth; on the other hand, autophagy may also facilitate proliferation and survival of tumor cells thus promoting tumor growth, invasion, and metastasis [ 85 , 86 ]. In recent years, more and more studies have shown that autophagy played a key role in the development of tumors, including cell proliferation, metastasis, and chemotherapy resistance [ 87 ].…”
Section: Lncrna As Regulators Of Autophagy In Neurological Diseasementioning
confidence: 99%